Theoretical insight of nitric oxide adsorption on neutral and charged Pd-n (n=1-5) clusters - Begum, Pakiza; Gogoi, Pranjal; Mishra, Bhupesh Kumar; Deka, Ramesh Chandra (International Journal of Quantum Chemistry, 2015)
Density functional theory (DFT) calculations within the framework of generalized gradient approximation have been used to systematically investigate the adsorption of nitric oxide (NO) molecule on neutral, cationic, and anionic Pd-n (n=1-5) clusters. NO coordinate to one Pd atom of the cluster by the end-on mode, where the tilted end-on structure is more favorable due to the additional electron in the * orbital. On the contrary, in the neutral and cationic Pd-2 system, NO coordinates to the bridge site of cluster preferably by the side-on mode. Charge transfer between Pd clusters and NO molecule and the corresponding weakening of NO bond is an essential factor for the adsorption. The NO stretching frequency follow the order of cationic>neutral>anionic. Binding energy of NO on anionic clusters is found to be greater than those of neutral and cationic clusters. (c) 2015 Wiley Periodicals, Inc.
Keywords: Density functional theory; electronic property; geometric configuration; NO adsorption; small palladium cluster